Search for charge-parity violation in semileptonically tagged D0 → K+π− decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Journal of high energy physics, 2025)
An analysis of the flavour oscillations of the charmed neutral meson is presented. The ratio of D0 → K+π− and D0 → K−π+ decay rates is measured as a function of the decay time of the D0 meson and compared with the charge-conjugated system to search for charge-parity violation. The meson flavour at production is double-tagged by the charges of the muon and pion in the preceding B overline → D∗(2010)+μ−X and D∗(2010)+ → D0π+ decays, respectively. These decays are selected from proton-proton collision data collected by the LHCb experiment at a centre-of-mass energy of 13 TeV and corresponding to an integrated luminosity of 5.4 fb−1. The flavour oscillation parameters, relating to the differences in mass and width of the mass eigenstates, are found to be y′ = (5.8 ± 1.6) × 10−3 and (x′)2 = (0.0 ± 1.2) × 10−4. No evidence for charge-parity violation is seen either in the flavour oscillations or in the decay, where the direct charge-parity asymmetry is measured to be AD = (2.3 ± 1.7) %.
Im Titel sind die Zahl "0" sowie die Plus- und Minuszeichen hochgestellt
The LHCb collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, F.C. Glaser, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascón, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, S.R. Roy, M. Ruiz Diaz, M.D Tat, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und viele weitere]
Gesehen am 16.10.2025